Qualitative Assessment of Surgical Repair of Three Types of Unilateral Cleft Lip - Adekunle M. Adetayo; Abdurazzak Olanrewaju Taiwo; Modupe Olusola Adetayo; Moses A. Akinola; Wasiu Lanre Adeyemo (Association of Support to Oral Health Research (APESB), 2022)
Objective: To assess the effect of the three types of unilateral cleft lip (UCL) [cleft lip only, cleft lip and alveolus, and cleft lip alveolus and palate] on the outcome of the repair. Material and Methods: This study was a case series of effect of types of UCL on the outcome of the repair. Fifteen subjects each were in three UCL phenotypes groups. Evaluation of the scar, lip, and nose was done qualitatively by both parents/guardians and professionals using a modified form of the criteria described by Christofides et al. (2006). Results: In the assessment of the surgical scar, the parents found a difference between the three types of cleft in terms of texture, shape, and width of the scar and presence of columella deviation. The professional assessors, however, only found the three types of cleft to be different in the presence of alar flattening. Conclusion: Differences truly exist in the outcome of surgical repair of the three types of unilateral cleft lip, especially in the aesthetics of the nose and in the width and shape of the residual lip scar. Thus, it is important to consider this in the assessment of UCL repair because putting the subtypes together might have a negative impact on the assessment.